solve any problem from the question pls solve it as soon as possible
Attachments:
![](https://hi-static.z-dn.net/files/d6a/fde60e17d9c59aef088ed9580f104338.jpg)
Answers
Answered by
1
Answer:
i) p(x) = 3x + 1 , x=1/3
ans) substitute the value
p(1/3) = 3(1/3) + 1 = 1 + 1 = 2
ii) p(x) = 5x - π , x=4/5
ans) p(4/5) = 5(4/5) - π = 4 - π
iii)p(x) = x²- 1 , x = 1 , -1
ans) p(1) = 1² - 1 = 0
p(-1) = (-1²) - 1 = 0
so like that substitute each value separately and find the answers mark as brainliest answer if you liked it
Similar questions